Minimalism Meets Luxury: Analyzing Uniqlo's Strategy in Enhancing Willingness to Pay and Brand Attachment - Rasid, Abdul; Tuti, Meylani (Business Management Analysis Journal (BMAJ), 2025)
This study investigates the impact of luxury brands, design, and brand awareness on willingness to spend and brand loyalty. This study takes a quantitative approach, including data gathered from a survey of Uniqlo customers. 220 respondents were gathered by accidental sampling, which involved purchasers who chance to meet the researcher. The questionnaires were distributed using Google Forms in November 2024 at different Uniqlo outlets in Jakarta and Bekasi. The findings of this study indicate that luxury brands have a considerable influence on willingness to pay and brand attachment, with design serving as the primary mediator. Brand awareness was also discovered to be an essential factor in developing brand connection, which boosts the desire to spend. However, the direct impact of design on willingness to spend is greater than that of premium brands and brand recognition. The outcomes of this study add to the body of theory by deepening our understanding of the interaction between branding aspects in the context of affordable luxury. In practice, this research provides insights for brands such as Uniqlo on how to prioritise innovative design and strong brand awareness strategies in improving consumer value.